Deskripsi Media yang Digunakan oleh Guru Kelas I dalam Modul Ajar Pembelajaran Membaca di SDN 9 Sungai Ambawang - Mudheri, Mudheri; Afryaningsih, Yunika; Listiarini, Yuni (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The learning media used includes human-based, print, visual, and audio-visual media, which are aimed at helping students understand the basic reading material. This study examines the use of learning media in teaching reading for grade 1 students of SDN 9 Sungai Ambawang, an elementary school in a rural area with limited facilities. This research uses a qualitative approach with a descriptive method, through observation and interviews with teachers. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The results showed that human-based media, such as lectures and discussions, were most predominantly used (56%), while visual and audio-visual media were underutilized (16% and 4%). Although the limitations of the means affect the use of more modern media, teachers' innovations in utilizing simple media are still effective in helping students learn to read. This study recommends increasing the use of visual and audio-visual media to increase students' interest and understanding, as well as the importance of paying attention to local contexts, including the use of regional languages in reading learning.